(untitled) - Gershon, Steven (Oxford, 2002)
English upgrade aims to help adult and young adult learners of English to speak the language more fluently, sound more natural and communicate more effectively. It does this by developing and extending learners' existing knowledge of English; guiding them to fluency through carefully controlled activities; and building their confidence through enjoyable and meaningful tasks. Components of "English Upgrade" 1, 2 and 3 are: student book with student audio CD; teacher's resource book - containing a course introduction, unit-by-unit teaching notes with answers, photocopiable communication activities, photocopiable reading files, a photocopiable list of key vocabulary, photocopiable progress tests, full answer keys to the workbook, and photocopiable audio scripts; workbook - containing reading and writing activities to consolidate the language introduced in the student book; and class cassette or CD - containing all the listening material in the course
Keywords: English language; Study and teaching